Industrialization and developing countries - Mountjoy, Alan B. (London : Hutchinson, 1975)
The book discusses brief summary of the theories of economic growth; economic concept of a whole country as a growth pole to the geographers' use of the idea in respect of particular urban centres or regions within a state; the spread of industrialisation; the state of industrialisation in particular countries; nature and value of industrial statistics; and distribution of manufacturing, nationally or globally.
Previous editions published under title: Industrialization and under-developed countries.
Includes bibliographical references and index.
lje 16/06/2017
Loans
Keywords: Industrial policy; Industrialization; Economic history; Developing countries